Contextual reinstatement affects semantic organization - Vaknin, Dana; Raz-Groman, Zohar; Scheuer, Alon; Sadeh, Talya (Frontiers in Psychology, 2023)
Abstract The Context Dependency Effect is the well-established finding in which memory performance is enhanced under conditions in which the encoding and retrieval contexts overlap (i.e., Same-Context) and diminished when the overlap between encoding and retrieval contexts is low (i.e., Different-Context). Despite much research on context-dependent memory, most prior work examined only mean performance levels. The current experiment examined the influence of context change, manipulated by using three different pieces of background music, on semantic organization during free recall. Recall driven by semantic organization captures an important, ecologically valid aspect of memory retrieval: because narratives of real-life events are typically comprised of semantically related concepts (e.g., “sea”, “bathing suit”, “sand” when recalling a trip to the beach), their recall is likely driven by semantic organization. Participants in the current study were tested in the Same or Different context as the material was learned. The results showed that although the mean number of correctly recalled items was numerically greater in the Same-Context condition compared to the Different-Context condition, the Context Dependency Effect was not significant. In contrast, however, semantic clustering—an established measure of semantic organization—was greater in the Different-Context condition compared to the Same-Context condition. Together, these results suggest that when contextual cues at recall are relatively meager, participants instead use semantic information as cues to guide memory retrieval. In line with previous findings, temporal organization, patterns of errors, and serial position analyses showed no differences between the two context conditions. The present experiment provides novel evidence on how external context change affects recall organization.